1980
DOI: 10.1159/000198478
|View full text |Cite
|
Sign up to set email alerts
|

Salivary and Gastric Secretions in Patients with Tropical Sprue

Abstract: Salivary secretions on mechanical stimulation with forced spitting method and on chemical stimulation with 10% citric acid and gastric acid secretions on maximal histamine stimulation were studied in 20 adults with tropical sprue and 20 adult control subjects. It was observed that the chemical method provided a better stimulus than the mechanical one in both groups. The salivary flow rates as well as salivary amylase, pH, sodium and potassium were similar in both groups. Tropical sprue patients, however, had s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Moreover, bacterial contamination in the jejunum was found to persist in these patients up to 4 months after the original infection [48]. One study reported reduced secretion of gastric acid in patients with TS, though salivary IgA was normal [49]. In another study, a proportion of patients with TS were found to have hypogammaglobulinemia [50].…”
Section: Why Does Bacterial Colonization Occur In Ts?mentioning
confidence: 99%
“…Moreover, bacterial contamination in the jejunum was found to persist in these patients up to 4 months after the original infection [48]. One study reported reduced secretion of gastric acid in patients with TS, though salivary IgA was normal [49]. In another study, a proportion of patients with TS were found to have hypogammaglobulinemia [50].…”
Section: Why Does Bacterial Colonization Occur In Ts?mentioning
confidence: 99%